Directional short wind wave spectra derived from the sea surface photography. Issue 9 (10th September 2013) - Yurovskaya, M. V.; Dulov, V. A.; Chapron, B.; Kudryavtsev, V. N.
<x xml:space="preserve">Abstract</x> [1] New field measurements of 2‐D wave number short wind wave spectra in the wavelength range from few millimeters to few decimeters are reported and discussed. The measurement method is based on stereophotography and image brightness contrast processing. As found, the spectra of decimeter waves are almost isotropic and weakly dependent on the wind speed. Both directional anisotropy and wind sensitivity rapidly increase at wave numbers larger than 100 rad/m. These aspects are consistent with other previously reported optical and radar data. Following these new in situ measurements, a revision of a semiempirical model of short wind wave spectrum is suggested. This revised model can readily be implemented in other studies (radar scattering, air‐sea interaction issues) where detailed knowledge of short wind wave spectra is crucial.